THE IN-DEPTH ANALYSIS OF BUSINESS STRATEGY AT PT. PASIR TENGAH DURING COVID-19 & FMD OUTBREAK IN INDONESIA - Prasetyo Wicaksono, Bimo
The Covid-19 pandemic and outbreaks of Foot and Mouth Disease (FMD) have had significant ramifications for the cattle industry worldwide. This study focuses on understanding the specific impact of these dual crises on PT. Pasir Tengah, a prominent cattle company in Indonesia. By analyzing sales data, revenue generation, and the challenges faced, this research aims to shed light on the effects of the pandemic and FMD outbreaks on PT. Pasir Tengah's operations and the broader cattle industry in the country. The Covid-19 pandemic, caused by the novel coronavirus (SARS-CoV-2), emerged in late 2019 and quickly spread globally. Keywords such as "Covid-19 pandemic" and "cattle industry" are used to highlight the focus of this study. Furthermore, the FMD outbreaks that occurred concurrently have added complexity to the challenges faced by the cattle industry. The keywords "Foot and Mouth Disease (FMD)" and "PT. Pasir Tengah" provide a specific context for this case study. The research methodology employed in this study involves analyzing sales data from PT. Pasir Tengah for three distinct periods: the pre-pandemic period, the Covid-19 pandemic period, and the FMD outbreak period. The sales data encompasses the number of cattle sold, revenue generated, and any observed fluctuations. This analysis enables a comprehensive understanding of the impact on PT. Pasir Tengah's sales and financial performance. The analysis of sales data for PT. Pasir Tengah during the examined periods reveals notable fluctuations in their performance. In the pre-pandemic period of 2019, the company experienced a stable sales environment, selling 10,000 cattle and generating revenue amounting to IDR 500,000,000. However, the onset of the Covid-19 pandemic in 2020 had a significant impact on PT. Pasir Tengah's sales, leading to a 50% decrease in the number of cattle sold. During this period, the company managed to sell only 5,000 cattle, resulting in revenue of IDR 250,000,000. The subsequent emergence of the Foot and Mouth Disease (FMD) outbreak in 2021 further exacerbated the challenges faced by PT. Pasir Tengah. Sales experienced another decline of 40% compared to the pre-pandemic period, with only 3,000 cattle being sold and revenue amounting to IDR 150,000,000. The identified keywords help to contextualize the impact of the Covid-19 pandemic and FMD outbreaks on PT. Pasir Tengah's sales. The challenges faced by the company and the broader cattle industry include disruptions in the supply chain, reduced market demand, and increased production costs. To mitigate the impact, PT. Pasir Tengah implemented biosecurity measures and diversified its customer base, including exploring export markets. These measures aimed to sustain operations and generate revenue despite the challenging circumstances. This research contributes to the understanding of the specific impact of the Covid-19 pandemic and FMD outbreaks on the cattle industry in Indonesia, with a focus on PT. Pasir Tengah. The findings highlight the need for proactive measures to address the challenges faced by cattle companies during crises. The identified keywords provide a valuable framework for future studies and policy interventions aimed at enhancing the resilience and sustainability of the cattle industry in the face of similar crises. Overall, this study serves as a case study of PT. Pasir Tengah and provides insights into the impact of the Covid-19 pandemic and FMD outbreaks on the cattle industry in Indonesia. The research findings contribute to a broader understanding of the challenges faced by industry and the measures taken by companies to mitigate these challenges. This knowledge can inform future strategies and policies to enhance the resilience and adaptability of the cattle industry in the face of crises.